Efekt kryminału. O rzeczywistości (w) gatunku = The impact of the crime novel. On the reality in/of the genre - Kraska, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper contains reflections on the reality in crime novels and the reality of the crime novel as a genre. The author tries to answer the question of why topics related to social and political issues, domestic violence, small scale and large scale history, gender issues etc. are so easy to fit into the genre of the crime novel. He also tries to determine the reasons for the emergence of the new "crisis narrative".
Keywords: kryminał; literaturoznawstwo